O Desvelamento do Mito Arturiano - Edileide Brito (Medievalista)
Attempt for King Arthur’s identity it is something irrelevant and and what it sends to us to enter in a complex universe. To rigour, the literature uses mythological materials like straight source of events and historical characters, in which the history is deformed by popular imagination, where it draws on the myth a profile like concretization of a Utopia, the fact of literary work to be a sort of concrete Utopia keeps alive the hope and the ideal. The literature affects us through the capacity to construct people, a world rises up around the limits of the reason and empirical description. Nevertheless, the myth is dynamic, it is transformed by the time whilst accompanying the spirit of time and the elements that do it a self-knowledge source are configurated in metaphor, depicting the essence of being. So, the mythical King Arthur became timeless and transcended the history. Consequently, the literature does that King Arthur does so that the King Arthur is not a King bequeathed to the past, but a king of the present, because so the measure that rescues the past of a literary work to understand it in the present, unconsciously is resurrected.